The Impact of Academic Load, Time Management, and Work-Study-Life Balance on Graduate Students' Anxiety Levels - Saputro, Gabrielle Goetama; Elisabeth, Grace; Khansa, Gadis (Dinasti Publisher, 2025)
Postgraduate students often face complex academic and professional pressures that can trigger anxiety and affect their mental well-being. This research purpose is to analyze the impact of academic workload, time management, also work-study-life balance on the anxiety levels of postgraduate students at Universitas Pelita Harapan. In this research, Author use a quantitive method which use a descriptive correlational and cross sectional approach. In this research, the populations is allof students in the Master of Management (MM) and/or Master of Hospital Administration (MARS) programs at Universitas Pelita Harapan (UPH), with a sample of 35 students selected using purposive sampling techniques. The results showed that the influence of Academic Workload on Student Anxiety was significant with a p-value of 0.038 (p < 0.05), the influence of Time Management on Student Anxiety was significant with a p-value of 0.041 (p < 0.05), and the influence of Work-Study-Life Balance on Student Anxiety was highly significant with a p-value of 0.000 (p < 0.05).